Mathematical Models of Systems - Rakhmatiloevna, Pulotova Mokhira; Otabekovna, Muzaffarova Gulsara (Researchparks Publishing, 2023)
Classification of control object models. There is a wide variety of model types and classes. None of the classification methods gives a complete picture and does not reflect all the properties of the models used, because it characterizes only individual features of the model.